Enhancing Social Media Adoption Among Food and Beverage Microenterprises: The Mediating Role of Perceived Initial Trust - Hernando, Hendrick; Yasirandi, Rahmat; Mataruka, Leo Tarambiwa (Universitas Airlangga, 2026)
Background: The availability of technological factors largely influences social media adoption as a business support tool for microenterprises worldwide. However, recent studies reveal inconsistencies in the direct influence of technological factors on social media adoption. The proposed mediating variable is essential to address those inconsistencies. Objective: This study aims to identify the mediating role of perceived initial trust in the nexus between technological factors and social media adoption. Methods: Data was collected from 200 owners or staff of Indonesian food and beverage (F&B) microenterprises using a close-ended online questionnaire. Partial least squares equation modeling (PLS-SEM) was utilized for the data analysis process. Results: Findings revealed that cost-effectiveness significantly influences social media adoption, while relative advantage and perceived compatibility have no significant direct impact. Based on the result of PLS-SEM, this study identified a full mediation role of perceived initial trust, especially for relative advantage and perceived compatibility. The presence of potential advantages and compatibility shapes users' decisions to adopt social media through their trust in the early stages. Conclusion: This study improves the understanding of how perceived initial trust connects technological factors to social media adoption. Furthermore, our study suggests practical implications for the government to create a community of practice involving F&B microenterprise owners. This suggestion may enhance knowledge and trust in the use of social media. Keywords: Social Media Adoption, Perceived Initial Trust, Technological Factors, F&B Microenterprises